Different inflammatory stimuli in the footpad of mice influence the kinetics of resident peritoneal cells - Palos, M. C.; Azevedo, M. C. A.; Thies, F. G.; Osugui, L.; Alvares, A. M.; Laurindo, M. F.; Russo, R. T.; Popi, A. F.; Mariano, M. [UNESP] (Springer Basel Ag, 2012)
Evidence from the literature that inflammation is a systemic biological phenomenon prompted us to investigate whether inoculation of different irritants to the footpad of mice might influence the kinetics of resident peritoneal cells.Mice were inoculated in the footpad at different time intervals with Mycobacterium bovis bacillus Calmette-Guerin (BCG), Ehrlich ascitic tumor cells or lipopolysaccharide (LPS), and resident peritoneal cells were analyzed by flow cytometry.The results indicate that different stimuli induced different responses in resident peritoneal cells. FoxP3 positive regulatory T cells increased drastically in number after BCG inoculation. Conversely, tumor cell inoculation induced a decrease in FoxP3-positive T cells in the peritoneal cavity, although this effect was not statistically significant. Results also show that cells from the paw migrate to the popliteal lymph node and to the peritoneal cavity. Yet, there are cells in the peritoneal cavity that migrate to the popliteal lymph node.These data show that cells from the peritoneal cavity are influenced by pathologies in remote regions of the animal. How this novel phenomenon influences overall immune responses, courses of infection and tumor growth are open to further investigation.
Keywords: Inflammation; Peritoneum; Ehrlich tumor; BCG; LPS; FoxP3